Effectiveness of focal vs. balloon radiofrequency ablation devices in the treatment of Barrett's esophagus. Issue 2 (April 2016) - Brown, Jesica; Alsop, Benjamin; Gupta, Neil; Buckles, Daniel C; Olyaee, Mojtaba S; Vennalaganti, Prashanth; Kanakadandi, Vijay Naag; Saligram, Shreyas; Sharma, Prateek
Background and aims: The safety and efficacy of radiofrequency ablation (RFA) in treatment of Barrett's esophagus (BE)-associated dysplasia has been well established. The effectiveness of focal and balloon RFA devices has not been compared. Therefore, the aim of our study was to assess the effectiveness of focal and balloon RFA devices in the treatment of BE by calculating absolute and percentage change in BE length with RFA therapy by comparing pre- and post-treatment BE length. Patients and methods: This is a retrospective cross-sectional study of patients who underwent at least one treatment with either focal and/or balloon RFA devices who were identified from two tertiary centers. Patients' demographics, hiatal hernia, pre- and post-treatment BE length, prior use of endoscopic therapies and number of sessions were recorded. Results: Sixty-one patients who had undergone 161 RFA treatment sessions met inclusion criteria. There was no significant difference in percentage change in BE length with greater number of RFA sessions. RFA with a focal device resulted in greater percentage reduction in BE length compared to the balloon system (73% vs. 39%, p < 0.01). After adjusting for initial BE length, pre-treatment BE length, hernia status, prior endoscopic mucosal resection (EMR), prior RFA, and prior EMR/RFA sessions, RFA with a focal device at each session remained an independent predictor for a significant reduction in BE extent as compared to the balloon system. Conclusion: The focal RFA device alone was more effective in treatment of BE compared to the balloon system, with a greater reduction in extent of BE. The focal RFA device for endoscopic eradication therapy of BE should be considered the preferred technique.